Sliding Mode Control with Gain-Scheduled for Magnetic Levitation System - Rudi Uswarman; Swadexi Istiqphara; Denny Hidayat T.N. (Universitas Ahmad Dahlan, 2019)
This paper presents a study of controlling magnetic levitation object using conventional sliding mode control (CSMC) and sliding mode control (SMC) with gain-scheduled. SMC with gain-scheduled aims to improve the robustness of the control system from disturbance. The CSMC simulation results show that output can follow the set point if there is no interference, but if the disturbance happens then there is overshoot and undershoot of 0.034 mm and 0.07 mm for disturbance 10 âˆ— sin (ð‘¡) and 20 âˆ— sin (ð‘¡). Then SMC with gain-scheduled shows excellent performance because the output can follow the reference even if it got disturbance of 10 âˆ— sin (ð‘¡) and 20 âˆ— sin (ð‘¡).